Host Cells Participate in the In Vitro Effects of Novel Diamidine Analogues against Tachyzoites of the Intracellular Apicomplexan Parasites Neospora caninum and Toxoplasma gondii - Leepin, Angela (American Society for Microbiology (ASM), 2008)
The in vitro effects of 19 dicationic diamidine derivatives against the proliferative tachyzoite stages of the apicomplexan parasites Neospora caninum and Toxoplasma gondii were investigated. Four compounds (DB811, DB786, DB750, and DB766) with similar structural properties exhibited profound inhibition of tachyzoite proliferation. The lowest 50% inhibitory concentrations were found for DB786 (0.21 μM against Neospora and 0.22 μM against Toxoplasma) and DB750 (0.23 μM against Neospora and 0.16 μM against Toxoplasma), with complete proliferation inhibition at 1.7 μM for both drugs against both species. DB750 and DB786 were chosen for further studies. Electron microscopy of N. caninum-infected human foreskin fibroblast (HFF) cultures revealed distinct alterations and damage of parasite ultrastructure upon drug treatment, while host cells remained unaffected. For true parasiticidal efficacy against N. caninum, a treatment duration of 3 h at 1.7 μM was sufficient for DB750, while a longer treatment period (24 h) was necessary for DB786. Pretreatment of tachyzoites for 1 h prior to host cell exposure had no effect on infectivity. However, pretreatment of uninfected host cells had a significant adverse effect on N. caninum proliferation: exposure of HFFs to 1.7 μM DB750 for 6, 12, or 24 h, followed by infection with N. caninum tachyzoites and subsequent culture in the absence of DB750, resulted in significantly delayed parasite proliferation. This suggests that either (i) these compounds or their respective active metabolites were still present after the removal of the drugs or (ii) the drug treatments reversibly impaired some functional activities in HFFs that were essential for parasite proliferation and/or survival.